Analysis of Factors Causing Obesity and Its Relation to the Level of Self-Care Independence in Students of SD Budi Murni 2 Medan Tuntungan District - Grace Mutiara; Roy Wilson Sihaloho (Benih : Journal of Midwifery, 2025)
Obesity is a disorder characterized by excessive accumulation of body fat tissue. Childhood obesity can continue into adulthood. According to Pi-Sunver in modern Nutrition in Health and Disease, in obese infants and children, about (26.5%) will remain obese in the next 20 years. Meanwhile, (80%) obese adolescents become obese adults. Adorable small, big obese. The phenomenon of increasing the prevalence of childhood obesity or obesity in Indonesia is very worrying. The phenomenon that is widely found in children, especially in big cities, in the middle and upper class communities occurs due to low public awareness in educating their children to live healthier lives by meeting their daily fiber intake needs, doing a lot of activity and exercising enough, and avoiding eating foods that are high in calories, such as: fast food and so on. In addition to the lack of efforts by the government and health institutions in communicating, disseminating information, and intensifying public education about the importance of a healthy lifestyle, the dangers of childhood obesity and obesity and the steps taken to prevent and treat overnutrition so that it can reduce the prevalence of childhood obesity and obesity in Indonesia. Indonesia is one of the developing countries that has experienced progress in the economic field due to the global market. Economic progress has a wide impact on people's social lives, including the tendency of people's lifestyles. Traditional lifestyles are considered no longer relevant to current conditions so that people's lifestyles tend to shift to a sedentary lifestyle. Unfortunately, in today's sedentary lifestyle, the proportion of physical activity is greatly reduced while food intake tends to be high in energy (fat, protein, and carbohydrates) and low in fiber. Conditions like this have a high chance of increasing the likelihood of diseases due to dietary deviations such as overnutrition and obesity. Based on the results of measuring the weight and height of students aged 7-9 years at SD Budi Murni 2 in 2025, there are 38 students who experience obesity in children aged 7-9 years, consisting of 12 students aged 7-8 years, 26 students aged 9 years. In 2025, there will be 47 students with an average weight of >35 kg and a height of ± 120 cm, consisting of 2 students who are 7 years old, 26 students who are 8 years old, 19 students who are 9 years old. Meanwhile, based on the source of Indonesian knowledge institutions, the ideal weight and ideal height for children aged 7-9 years is 24 kg and the ideal height is 120 cm, it can be concluded that the number of students who experience obesity every year has increased.